Implicit LES for Supersonic Microramp Vortex Generator: New Discoveries and New Mechanisms. (24th February 2011) - Li, Qin; Liu, Chaoqun
Abstract : This paper serves as a summary of our recent work on LES for supersonic MVG. An implicitly implemented large eddy simulation (ILES) by using the fifth-order WENO scheme is applied to study the flow around the microramp vortex generator (MVG) at Mach 2.5 andRe   θ = 1440 . A number of new discoveries on the flow around supersonic MVG have been made including spiral points, surface separation topology, source of the momentum deficit, inflection surface, Kelvin-Helmholtz instability, vortex ring generation, ring-shock interaction, 3D recompression shock structure, and influence of MVG decline angles. Most of the new discoveries, which were made in 2009, were confirmed by experiment conducted by the UTA experimental team in 2010. A new 5-pair-vortex-tube model near the MVG is given based on the ILES observation. The vortex ring-shock interaction is found as the new mechanism of the reduction of the separation zone induced by the shock-boundary layer interaction.